Endovascular management of pediatric neurovascular malformations – A single?center experience from South India - Kalvala, Abhinav; Sivaraman, Rajakumar Padur; Tarikare, Shruthi; Sankaranarayanan, Shuba; Joseph, Santhosh (Indian Journal of Child Health, 2019)
Background: Neurovascular malformations (NVMs) in pediatric population are highly challenging to manage and treatment options include open surgery, endovascular therapy, and radiosurgery or combined. Recently, there has been a gradual shift from conventional surgical approach toward endovascular therapies with increasing availability of technical expertise and gadgetry. Objective: We aimed to study the clinical profile and immediate outcome of children with NVMs, who underwent endovascular therapy. Materials and Methods: This retrospective observational study was conducted in a tertiary care center in South India between February 2017 and August 2018. We included children admitted in pediatric intensive care unit (PICU) with NVM and needed neuroradiological intervention. Children with thromboembolism or other NVMs who did not require intervention were excluded from the study. Data on clinical profile, endovascular procedure done, supportive therapy given, and immediate outcome were collected and analyzed. Results: Of 1615 children admitted in PICU, 13 had NVM (0.8%), of which five had arteriovenous malformation (AVM), three had vein of Galen arteriovenous malformation (VGAM), one had VGAM with dural AVM, one had acquired carotid-cavernous fistula, two had berry aneurysm, and one had mycotic aneurysm. VGAM presented as hydrocephalus, whereas AVM and aneurysm as intracranial hemorrhage. Endovascular embolization was done using platinum detachable coils, onyx, N-butyl cyanoacrylate glue, and coil assist stents. One child needed decompressive craniectomy and another child needed extraventricular drainage. Four children needed pre-procedure ventilation and seven children needed prolonged post-procedure ventilation. Mortality was 15%; and among the survivors, 72% had an uneventful recovery. One child had seizures and two had hemiparesis at discharge. Conclusion: Endovascular management is an effective intervention for pediatric NVM. Multidisciplinary team approach and good pediatric intensive care are important for successful outcome. Further studies with long-term follow-up are needed to assess the durability of endovascular therapy.